Two long non-coding RNAs, CAT179 and CAT1796, differentiate between benign prostate hyperplasia and prostate cancer - Ebrahimi, Nasim; Amirmahani, Farzane; Akbari, Maryam; Mosharaf Ghahfarokhi, Azin; Hajihashemi, Bahareh; Hamblin, Michael R. (Archives of Biological Sciences, 2021)
Paper description: Early diagnosis of prostate cancer is crucial for appropriate treatment selection. Long non-coding RNAs (lncRNAs) are considered as potential biomarkers in cancers for early diagnosis. The expression of lncRNAs CAT179 and CAT1796 is significantly higher in prostate cancer. CAT1796 lncRNA could be a prostate cancer biomarker. Abstract: Several long non-coding RNAs (lncRNAs) have recently emerged as potential biomarkers in cancer biology. In the present study, we examined the expression of four lncRNAs (CAT179, CAT1796, PRCAT47, and CAT1066) to evaluate their ability to discriminate prostate tumors from benign prostate hyperplasia (BPH). Expression of these four lncRNAs was examined in 20 prostate cancer and 20 benign prostate hyperplasia (BPH) samples, as well as in urine samples (11 BPH, and 11 cancer). Total RNA was extracted for cDNA syntheses. The expression of the candidate lncRNAs was evaluated by quantitative real-time PCR (qRT-PCR). The lncRNAs CAT1796 and CAT179 were both upregulated in prostate cancer compared to BPH clinical samples (P<0.05). ROC curve analysis showed that CAT1796 had high sensitivity and specificity for diagnosis of prostate cancer (AUC=0.8151[95%CI 0.65-0.97]), suggesting that CAT1796 lncRNA could be a prostate cancer biomarker.